COMPARATIVE ANALYSIS OF STRATEGIC MANAGEMENT IN DEFENSE PLANNING FOR INDONESIA AND POLAND - Sari, Maya Rizki; Kautsar, M. Haikal (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2021)
Besides the same red and white flag, Indonesia and Poland share a similar historical setting which includes revolutions, wars of independence, and the promotion of national unity. Indonesia has succeeded in reforming and demonstrating show the true democracy in the international community. While Poland was succeeding in making changes by turning into a constitutional state after being freed from communism. On the other hand, Poland was the only European economy to escape from the 2008 recession. Since the fall of the communist regime, based on the existing historical struggles and capacity of the Polish state which knew how to leave the communist state and its successes in the economic field, the Researchers is interested in the search for the comparison between the management defense strategies in Indonesia and that of Poland. The purpose of this study is to see a comparison of strategic management in defense planning for Indonesia and Poland. The method used is qualitative. Regarding the trend in the development of the strategic environment or the estimation of the lack of possibilities for traditional military tangible threats mentioned explicitly in the Defense White Paper of the Republic of Indonesia and the Polish State Defense White Paper. The results of the study showed that the use of defense diplomacy instruments became dominant. In addition to developing defense policies and defense planning in the form of strengthening Indonesia's defense structure and posture comprehensive. Indonesia needs to strengthen defense capabilities in the Southeast Asian countries by strengthening the basis of posture and defense structures associated with the vision of the world's maritime axis. Thus, a sustainable Essential Minimum Force (MEF) is achieved